A research annual - Samuels, Warren J., 1933-; Biddle, Jeff; Emmett, Ross B. (Research in the history of economic thought and methodology ;, 2005)
Volume 23A of this research annual first presents two articles on Adam Smith, one on his use of the concept of the invisible hand, and another on his use of Isaac Newton's methodology; an article on rival conceptions of distribution: in the 20th century; and a set of introductory notes to the study of the history of economic thought. Secondly, the volume presents multiple review essays on a book on the history of institutional economics, and single review essays on a variety of books, including books on causality, economic thought and the making the European monetary union, the Scottish Enlightenment, economic justice and theological values, a dictionary of economic quotations, economic morality, Thomas Reid, policy making, and autobiographical essays by Nobel laureates in economics.